Die EG-Umwelt-Audit-Verordnung - Anreiz zu Innovationen oder zu potemkinschen Dialogen? - Jens Hemmelskamp; Uwe Neuser (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1994)
Since 13 July 1993 the EC eco-audit regulation has regulated voluntary participation of enterprises in eco-auditing. As. yet it is a vague plan for environmental management systems and eco-auditing of enterprises, which in practice, when it comes to implementing it, may be interpreted in many different ways. The European Council's aim of promoting a steady improvement of environmental standards in enterprises with the help of this regulation can only be achieved in part. It is to be feared that instead of the desired problem-oriented analysis of weaknesses, an objective-oriented approach to secure a document certifying participation will prevail on the part of the enterprises. The inadequate description of the nature of the auditing may result in a watering down of the requirements. Such a development in terms of the implementation could tarnish the public image of this tool designed for environmental protection and lead people to consider it a swiz. To prevent this from happening the further elaboration of the regulation should continue to be a dynamic Iearning process, taking into account future practical experience. Moreover, eco-audits must not be regarded as substitutes for necessary tools of a market economy in the sphere of environmental policy.
Keywords: 330